Morfologia de plântulas e estádios juvenis de espécies invasoras - Mourão, Káthia Socorro Mathias; Domingues, Laércio; Marzinek, Juliana [UNESP] (Universidade Estadual de Maringa, 2007)
The morphology of 20 species of weeds that occur in the most common crops in Maringá, Paraná State, Brazil and adjacent regions were described at early developmental stages, in order to identify the species in the field and provide information for taxonomic and ecological works. Sixteen species featured epigeal-foliaceous seedlings. The seedling in Cardiospenuum halicacabum is epigeal-fleshy; in Cenchrus echinatus and Digitaria horizontalis it is hypogeal and in Commelina virginica is epigeal-cryptocotyledonar. The differentiation of the first eophyll occurred within ten (Digitaria horizontalis) to 35 days (Bidens pilosa) and the first metaphyll appeared within 22 (Commelina virginica) to 49 days (Acanthospenuum australe). The number of eophylls varied from one to four, and the phyllotaxis varied from alternate to opposite.
Morphology and development of seedlings and saplings of weeds
Keywords: Morphology; Sapling; Seedling; Weed; Acanthospermum australe; Bidens pilosa; Cardiospermum halicababum; Cenchrus echinatus; Commelina; Commelina virginica; crop; Digitaria horizontalis; morphology; plant; plant development; seedling; weed